A National Survey of the Oral Health Status of Homeless Veterans - Gretchen Gibson, DDS, MPH; Robert Rosenheck, MD; John B. Tullner, DDS, FICD; (Blackwell Synergy, 2003)
This study reports results from a survey designed to (1) ass= the oral health needs of a national sample of homeless veterans and (2) compare the dental needs of homeless veterans participating in VA-sponsored rehabilitation programs with domiciled veterans in VA substance addiction programs